Initial characterization of immune microenvironment in pheochromocytoma and paraganglioma - Jin, Bo; Han, Wencong; Guo, Jingjing; Tian, Jie; He, Shiming; Gong, Yanqing; Zhou, Jingcheng; He, Qun; Shen, Qi; Zhang, Zheng (Frontiers in Genetics, 2022)
Due to fewer adverse events, faster onset of action, and longer durable responses compared to chemotherapy, immunotherapy has been widely used to treat advanced solid tumors. Moreover, immunotherapy can improve the autoimmune status, thus allowing patients to benefit from the treatment in the long term. The immune microenvironment status is closely associated with the response to chemotherapies. Here, we analyzed the characteristics of the immune microenvironment in pheochromocytoma and paraganglioma (PPGL). Immunohistochemistry showed that PD-L1 is sparely expressed in PPGL with low positive rates and low expression levels, an expression pattern, that is, not correlated with tumor malignancy. Moreover, the level of intratumoral CD4+ and CD8+ lymphocyte infiltration in PPGL is low, suggesting that the immune microenvironment in PPGL may be in “immune desertification” or “immune rejection” states in which CD4+ and CD8+ lymphocyte infiltration is prevented, rendering immunotherapy less effective. In sum, our results indicate that PPGL is a microsatellite-stable tumor with low tumor mutational burden (TMB) levels, weak neoantigen production, and poor tumor antigenicity, hinting at a poor response of PPGL to chemotherapies.